2018
DOI: 10.1002/jmri.26270
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Diffusion and Perfusion in Vertebral Bone Marrow Using Intravoxel Incoherent Motion (IVIM) With Multishot, Readout‐Segmented (RESOLVE) Echo‐Planar Imaging

Abstract: Technical Efficacy Stage: 1 J. MAGN. RESON. IMAGING 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…On average, we measured the perfusion fraction ( f ) to be 0.109 ± 0.043 in the SOC of the control femoral heads, which is similar to the f values measured in prior vertebral bone marrow perfusion studies using IVIM. For example: using a similar fat‐suppressed RESOLVE‐DWI sequence, Lasbleiz et al 32 measured an average vertebral bone marrow f value of 0.145 ± 0.054 in healthy adults; and healthy adult studies by Marchand et al 25 and Liu et al 33 measured average vertebral bone marrow f values of 0.140 ± 0.06 and 0.142 ± 0.011, respectively. Meng et al 26 evaluated IVIM perfusion of the femoral head in children 6–24 months old with developmental dysplasia of the hip and measured a high average perfusion fraction ( f ) of 0.521 ± 0.090 in the control femoral heads.…”
Section: Discussionmentioning
confidence: 99%
“…On average, we measured the perfusion fraction ( f ) to be 0.109 ± 0.043 in the SOC of the control femoral heads, which is similar to the f values measured in prior vertebral bone marrow perfusion studies using IVIM. For example: using a similar fat‐suppressed RESOLVE‐DWI sequence, Lasbleiz et al 32 measured an average vertebral bone marrow f value of 0.145 ± 0.054 in healthy adults; and healthy adult studies by Marchand et al 25 and Liu et al 33 measured average vertebral bone marrow f values of 0.140 ± 0.06 and 0.142 ± 0.011, respectively. Meng et al 26 evaluated IVIM perfusion of the femoral head in children 6–24 months old with developmental dysplasia of the hip and measured a high average perfusion fraction ( f ) of 0.521 ± 0.090 in the control femoral heads.…”
Section: Discussionmentioning
confidence: 99%
“…After anatomical T1-weighted and T2-weighted MRI acquisitions, VBM-IVIM measurements were carried out on the lumbar spine of six healthy, young volunteers (age range 18-29 years, mean age 26.1±4.0 years, three women and three men). VBM-IVIM MRI was performed in sagittal orientation using the RESOLVE sequence, with the parameters proposed by Lasbleiz et al [13]; here briefly: repetition time 2400 ms, echo time 58 ms, field of view (FOV) 400 × 400 mm 2 , matrix size 188 × 188, slice thickness 6 mm (10 slices), seven bvalues of 0,50,100,150,400,800,1000 s/mm 2 , iPAT 3, and the Spectral Attenuated Inversion Recovery (SPAIR) fat saturation. Two repeated, identical RESOLVE acquisitions were performed on five volunteers.…”
Section: Mr Imagingmentioning
confidence: 99%
“…Further developments in VBM-IVIM data acquisition have been recently presented by Lasbleiz et al [13]. First, it was shown that an improved image quality, in terms of better spatial resolution and reduced susceptibility artifacts, could be obtained by employing a multi-shot readout-segmented EPI (RESOLVE [14], readout segmentation of long variable echo train) instead of the single-shot EPI, which had been used in all previous VBM-IVIM studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marrow ADC values also decrease from L1 to L5 in line with increasing fat and decreasing perfusion from the upper to the lower lumbar region. 97 ADC values in middle-aged to elderly patients with normal BMD were 0.47 AE 0.03; those with osteopenia were Fig. 7 Typical time-intensity perfusion curves of vertebral body marrow perfusion from dynamic contrast-enhanced magnetic resonance imaging examination in subjects with (a) normal bone mineral density (BMD), (b) low bone mass (osteopenia), and (c) osteoporosis.…”
Section: Bone Marrow Perfusionmentioning
confidence: 99%